Learning Strategies at MI Muhammadiyah 1 Sedayulawas During Covid-19 Pandemic - Alfi Nur Hidayati; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study is to describe the learning carried out during the pandemic. This research uses descriptive qualitative methods, with the aim of finding and extracting information about ongoing problems or problems discussed related to the covid-19 pandemic. Online learning is a solution to continuing to carry out teaching and learning activities, but it is only temporary due to many factors, both from internal and external. However, to overcome this problem, learning is carried out face to face by complying with health protocols and learning for no more than 4 hours, thus teaching and learning activities can still run smoothly, altouhgt not as usual.